Risk of Atrial Fibrillation in Young Adults With Isolated Diastolic, Isolated Systolic, and Systolic-Diastolic Hypertension. Issue 5 (November 2021) - Lee, So-Ryoung; Han, Kyung-Do; Choi, Eue-Keun; Ahn, Hyo-Jeong; Oh, Seil; Lip, Gregory Y.H.
Abstract : There is limited evidence regarding the risks of incident atrial fibrillation (AF) associated with stage 1 isolated systolic hypertension (ISH), isolated diastolic hypertension (IDH), and systolic-diastolic hypertension (SDH), especially among young adults. We aimed to evaluate the association between early stage of hypertension and AF in young adults. From the Korean nationwide health screening database, 2 958 544 subjects aged 20 to 39 years who were not prescribed antihypertensive medication at the index examination in 2009 were included. Subjects were categorized into 8 groups according to the 2017 American College of Cardiology/American Heart Association blood pressure (BP) guidelines: normal BP, elevated BP, stage 1 IDH, stage 1 ISH, stage 1 SDH, stage 2 IDH, stage 2 ISH, and stage 2 SDH. The primary outcome was new-onset AF. During a median follow-up of 8.3 years, 7347 subjects had incident AF (0.3 per 1000 person-years). Compared with normal BP, stage 1 IDH (adjusted hazard ratio, 1.160 [95% CI, 1.086–1.240]) and stage 1 SDH (1.250 [1.165–1.341]) were associated with higher risks of incident AF, but not stage 1 ISH. Stage 2 IDH, ISH, and SDH were associated with higher risks of incident AF by 24%, 37%, and 61%, respectively. Stage 1 IDH and SDH were associated with higher risks of incident AF compared with normal BP. The risk of incident AF with stage 2 IDH was similar to that of stage 1 SDH. Optimal BP control, including diastolic BP, is associated with the lowest risk of new-onset AF, even among young adults. Abstract : Supplemental Digital Content is available in the text.